2012
DOI: 10.1021/jp306186y
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Ruthenium-Dye-Sensitized TiO2 Surfaces Exposing the (001) or (101) Faces: A First-Principles Investigation

Abstract: We present a first-principles computational investigation on the adsorption mode and electronic structure of the highly efficient heteroleptic ruthenium dye C101, [NaRu(4,4′-bis(5-hexylthiophene-2-yl)-2,2′-bipyridine)(4carboxylic acid-4′-carboxylate-2,2′-bipyridine)(NCS) 2 ], on anatase TiO 2 models exposing the (001) and ( 101) surfaces. The electronic structure of the TiO 2 models shows a conduction band energy upshift for the (001)-surface ranging between ∼50 and ∼110 meV compared with the (101) surface, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 57 publications
8
57
0
Order By: Relevance
“…Laskova et al also reported that the surface concentration (0.4-0.5 molecules nm −2 ) of C101 dye [cis-bis(isothiocanate)(4,4 -bis(5-hexylthiophene-2-yl)-2,2 -bipyridi-ne)(4-carboxylic acid-4 -carboxylate-2,2 -bipyridine) ruthenium-(II) sodium] was lower on TiO 2 (0 0 1) nanosheets than that on TiO 2 (1 0 1) nanoparticles (0.7-0.8 molecules nm −2 ) [61]. Recent first-principle theoretical calculations suggested that the observed smaller dye coverage on the {0 0 1} facets than that on the {1 0 1} facets is a consequence of a partial contact of the thiophene and alkyl bipyridine substituents of C101 with the TiO 2 surface [59]. Compared with those systems, Ruthenizer 470 does not have bulky substituents and its surface concentrations on the TMC samples are quite low (e.g., 0.023 molecules nm −2 for TMC-4).…”
Section: Dye-sensitized H 2 Evolution Under Visible-light Irradiationmentioning
confidence: 97%
See 1 more Smart Citation
“…Laskova et al also reported that the surface concentration (0.4-0.5 molecules nm −2 ) of C101 dye [cis-bis(isothiocanate)(4,4 -bis(5-hexylthiophene-2-yl)-2,2 -bipyridi-ne)(4-carboxylic acid-4 -carboxylate-2,2 -bipyridine) ruthenium-(II) sodium] was lower on TiO 2 (0 0 1) nanosheets than that on TiO 2 (1 0 1) nanoparticles (0.7-0.8 molecules nm −2 ) [61]. Recent first-principle theoretical calculations suggested that the observed smaller dye coverage on the {0 0 1} facets than that on the {1 0 1} facets is a consequence of a partial contact of the thiophene and alkyl bipyridine substituents of C101 with the TiO 2 surface [59]. Compared with those systems, Ruthenizer 470 does not have bulky substituents and its surface concentrations on the TMC samples are quite low (e.g., 0.023 molecules nm −2 for TMC-4).…”
Section: Dye-sensitized H 2 Evolution Under Visible-light Irradiationmentioning
confidence: 97%
“…During this key step, electrons are preferentially injected into the {1 0 1} facet, which has a CB level lower by ca. 0.05-0.1 V than that of the {0 0 1} facet [58,59]. Finally, electrons are trapped by Pt and consumed in H + reduction.…”
Section: Dye-sensitized H 2 Evolution Under Visible-light Irradiationmentioning
confidence: 98%
“…Finally, the sensitizer's grafting group should establish a stable binding of the dye onto the metal oxide surface, thus ensuring long-term stability of the cell [163][164][165]. Investigation of the adsorption of organic dyes onto TiO2 cluster models [161,162,166], has largely shown that the bidentate bridging adsorption mechanism with proton transfer to a nearby surface oxygen is the energetically favored one (Figure 6), while the monodentate anchoring is usually predicted to be less stable, although some dependency on the employed methodology can be outlined [166], For Ru(II) sensitizers different adsorption modes onto the TiO2 surface can be found: while homoleptic dyes, such as N3 or N719, can adsorb on TiO2 using carboxylic anchoring groups residing on different bipyridine ligands and hence using up to three carboxylic groups (Figure 6c) [159,167], heteroleptic dyes, e.g., N621, C106, or Z907, necessarily adsorb via carboxylic groups residing on the same bipyridine (two carboxylic groups, Figure 6d) [168,169]. From an electronic structure point of view, when a dye is anchored to a semiconductor surface, two effects might interplay: (i) the electrostatic (EL) effect, due to the dye dipole moment; and (ii) the effect of the CT between the dye and the semiconductor, which may accompany the dye/semiconductor bond formation.…”
Section: Dye/tio2 Interfaces In Dscsmentioning
confidence: 99%
“…The large surface area and high crystallinity are usually required for high dye adsorption capability and rapid electron transport. Faceted anatase TiO2 single crystals with unique surface atomic and electronic structure were also introduced into the electrodes of DSCs [134][135][136][137][138][139][140][141][142][143][144][145][146][147][148][149]. Many researches used faceted anatase TiO2 crystals to fabricate photoanodes.…”
Section: Dye-sensitized Solar Cellsmentioning
confidence: 99%
“…From Mott-Schottky (MS) plots, the flatband potential value of {001} facet was negatively shifted by 0.06 V compared to that of {101} facet. Later, De Angelis et al presented a first-principles computational investigation on the adsorption mode and electronic structure of the dye C101 on anatase TiO2 {001} and {101} facet [142]. They theoretically confirmed the negative flatband shift of {001} facet, and explained that the slower charge recombination was attributed to the different dye-anchoring geometries of C101 on {001} and {101} facets ( Furthermore, the plane surface has superior reflectance ability, which can increase the light harvesting of photoanode.…”
Section: Dye-sensitized Solar Cellsmentioning
confidence: 99%